2011
DOI: 10.1097/brs.0b013e3181d2dec2
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Upright Posture Induces Degenerative Changes in Intervertebral Discs of Rat Cervical Spine

Abstract: Upright stance accelerates cervical disc degeneration in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…It is well established that physiological mechanical loads are beneficial for disc biology, whereas non-physiological loads can initiate and accelerate disc degeneration [ 11 13 ]. Previously, a foreleg amputation-induced rat disc degeneration model showed increased senescent cells within the degenerative disc [ 14 16 ]. These studies indirectly indicated that excessive and continuous mechanical compression caused by prolonged upright postures may aggravate cellular senescence within the disc.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that physiological mechanical loads are beneficial for disc biology, whereas non-physiological loads can initiate and accelerate disc degeneration [ 11 13 ]. Previously, a foreleg amputation-induced rat disc degeneration model showed increased senescent cells within the degenerative disc [ 14 16 ]. These studies indirectly indicated that excessive and continuous mechanical compression caused by prolonged upright postures may aggravate cellular senescence within the disc.…”
Section: Introductionmentioning
confidence: 99%
“…This environment elicits a range of pathological responses from NP and AF cells including dysregulation of NP‐marker genes such as ACAN and COL2A1 as well as more general processes such as autophagy, senescence, and apoptosis . Concurrently, degenerative NP and AF cells increase the expression of matrix degrading enzymes including matrix metalloproteinases (MMPs) −1, −3, −7, −9, −10 −13 and a disintegrin and MMP with thrombospondin motifs (ADAMTS) −1, −4, −5, −9, and −15 . This further accelerates loss of type II collagen and PG rich ECM and replacement with fibrous, type I collagen scar‐like tissue.…”
Section: Ivd Structure Function and Degenerationmentioning
confidence: 99%
“…7 The NP matrix consists of an irregular mesh of type II collagen and elastin fibers with abundant and highly hydrophilic proteoglycans, most significantly aggrecan. [8][9][10][11][12] DIVD commonly results in a change from type II to type I collagen and a decrease in proteoglycan content leading to dehydration of the NP, 13 an increase in expression of matrix degrading enzymes, [14][15][16][17] an upregulation of inflammatory cytokines [18][19][20] and an increase in cell senescence and apoptosis. [21][22][23] Adult NP cells cultured in NC cell conditioned media (NCCM) showed an upregulation of aggrecan, type II collagen, CD44, link protein and tissue inhibitor of metalloproteinase 1 (TIMP1).…”
Section: Introductionmentioning
confidence: 99%